NEGARA DALAM PANDANGAN FILSAFAT JAWA - Ariani, Iva (Yogyakarta, 2010)
Human is a “political animals” or animal that like doing politics. Politics is one of the human interaction type that involve a party that get and run power on another. Since last years ago in oppose of danger, disaster and defend alive, earn life with continue breed, human can not live alone, human needs groups and push their soul that causes them must societal alive. Javanesse culture also give contribution towards politics development and opinions about existence a country along with right and the duty. The subject policies culture in the eyes of java culture actually can be studied from ethics. Javanesse politics philosophy proposes that element of king, people and god be unitary can not dismember one another. The power of king usually has been connected with the king. The power of king will not come off hand but pass struggle that shiver from individual king or administrator concerned because the individual great that is the king get support from the people for example people figures priests. The sign of the success in this effort if he is success gets “wahyu or pulung“. Pulung is the country power symbol. Therefore after all the great somebody reaches after pulung, latest rule doesn't reside in his hand but on hand’s god.